Analisis Pengembangan Usaha Kecil dan Menengah di Lingkungan Berpenghasilan Rendah - Ali Avvienceena Al Attqia; Arifudin Arifudin; Moh. Haikal Jamaludin; Tegar Fiki Haikal; Rizki Bayhaqi (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This study aims to analyze the challenges and development strategies of micro, small, and medium enterprises (MSMEs) located in low-income areas in Indonesia. MSMEs play an important role in the Indonesian economy, but in areas with low income levels, MSMEs face various constraints, such as difficulties in accessing adequate capital, technology, and management skills. To conduct this study, the researchers used a qualitative approach by collecting data from various sources of relevant scientific literature. The results showed that MSMEs in low-income settings face several key constraints, including difficulty accessing formal sources of financing, limited use of information technology, and low implementation of good business management practices, such as in marketing and financial record-keeping. To be able to develop MSMEs in low-income environments, comprehensive efforts are needed, such as facilitating MSME access to official funding sources, providing training and assistance in the use of information technology, and improving MSME skills in implementing good business management practices. In addition, the availability of skilled human resources, as well as innovation and creativity are also important factors in supporting the growth of MSMEs in low-income areas. By paying attention to these various aspects, it is expected that the development of MSMEs in low-income environments can run effectively and provide optimal benefits to the regional and national economy, through collaboration and synergy between MSMEs, government, financial institutions, and other stakeholders.